2020
DOI: 10.1111/jvim.15983
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of point‐of‐care crossmatching methods and crossmatch incompatibility in critically ill dogs

Abstract: Background: The performance of commercial point-of-care crossmatch (CM) tests compared to laboratory tube agglutination CM is unknown. Additionally, there is limited information regarding CM incompatibility in ill dogs. Objectives: To determine if point-of-care major CM methods are accurate in detecting compatible and incompatible tests when compared to laboratory CM methods, and to identify factors associated with CM incompatibility in dogs. Animals: Part 1 (prospective) included 63 client-owned dogs potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 26 publications
1
35
1
Order By: Relevance
“…85,90,94 As mentioned previously, variation in crossmatch technique complicates evaluation of the existence and clinical relevance of those alloantibodies in dogs. 93,[98][99][100]105 3.6.4…”
Section: Agreement: 13/13 Evidence Summarymentioning
confidence: 99%
“…85,90,94 As mentioned previously, variation in crossmatch technique complicates evaluation of the existence and clinical relevance of those alloantibodies in dogs. 93,[98][99][100]105 3.6.4…”
Section: Agreement: 13/13 Evidence Summarymentioning
confidence: 99%
“…This is often referred to as the gold standard, but it has also been suggested that this method is too sensitive and identifies also clinically irrelevant incompatibilities. 53 The addition of antiglobulins might even has enhanced the agglutination reaction. 53,54 Therefore, it is uncertain whether this increases the sensitivity in detecting clinically relevant or irrelevant antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies utilizing a similar SL technique yielded incompatibility rates of only 17%–38% for major crossmatches and 17%–45% for minor crossmatches. The institutional rates were higher than historical SL rates, even when previous transfusion status was taken into account 6,9–10,20 . Therefore, we wished to investigate this discrepancy of the SL test performed at the authors’ institution to another SL technique performed at a commercial laboratory.…”
Section: Introductionmentioning
confidence: 94%
“…Many practitioners choose not to crossmatch transfusion‐naïve dogs due to the clinical observation that dogs lack clinically significant alloantibodies prior to initial transfusion. However, ongoing discoveries of new canine RBC antigens have led some to recommend crossmatching prior to all transfusions 4,9,19–20 . While many studies explore the compatibility results of various crossmatch tests in vitro, to the authors’ knowledge the sensitivity/specificity of these tests to predict clinically relevant transfusion reactions is unknown 6,9,15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation